Study of the Construction Sequence of Overlapping Tunnels by the Shield Tunneling Method: A Case Study of the Longest Overlapping Tunnel in China - Zhiyong Yang; Yaowen Ding; Yusheng Jiang; Kuanda Fang; Linwei Dong; Weiqiang Qi; Zheng Wei (Advances in Civil Engineering)
In this study, the reasonable construction sequence of an overlapping tunnel shield is investigated. Taking the overlapping tunnel of Tianjin Metro Line 5 as the background, a three-dimensional numerical model was established using Flac3D software to study the influence of the “first up and then down” and “first down and then up” construction sequences of the overlapping tunnel on the surface settlement, stratum displacement, lining radial stress, and displacement. The research results show that the shape and width of the final settlement tank on the ground under the two conditions are basically the same, and the difference between the maximum cumulative settlements is small. The accumulated ground settlement caused by the first up and then down construction sequence is 1.8 mm larger than that caused by the first down and then up sequence. The difference between the two working conditions on the vertical displacement of the stratum mainly occurs in the middle stratum of the upper and lower tunnels, and the proportion of the strata in the uplifted state and subsidence state is different. The construction sequence has little effect on the radial stress on the lining of the upper and lower tunnels. Under these two conditions, the excavation of the second tunnel causes a small change in the radial stress of the preceding tunnel lining, both within 4.2%. Under the working condition of first down and then up, the construction of the second tunnel causes the lining of the preceding tunnel to rise by 7.2∼9.2 mm. Under the condition of first up and then down, the construction of the second tunnel causes the lining of the preceding tunnel to sink again by 9.1∼10.4 mm. By comparing the effects of the two working conditions on the stratum and the tunnel lining, it is recommended that the construction be carried out in the order of first down and then up.